Perbandingan Metode Sequential Searching Dan Metode Turbo Boyer Dalam Pencarian Data Siswa Di Sekolah - Cahyono, Trisna; Yulianti , Liza; Yupianti (Jurnal Komputer, 2023)
SMA Negeri 11 Kota Bengkulu is one of the public high schools in Bengkulu City. Student data processing at SMA Negeri 11 Bengkulu City already uses computerized and integrated applications, but this data processing does not include processing problem student data. Where the management of problematic student data still uses bookkeeping and there is a violation point system that is recorded manually by the Guidance Counseling (BK) Teacher in the book. At the end of each school year, all points will be accumulated, to find out problem students. However, this is an obstacle where it takes time to calculate the violation points and search for student data because you have to look at one by one the book sheets that have been recorded manually. Comparison of the Sequential Searching method and the Turbo Boyer method in searching student data at school based on the processing time that occurs during the search process. In helping the comparison process, a student data search application was built at SMA Negeri 11 Bengkulu City using the Visual Basic .Net programming language and SQL Server Database. The student data search application at SMA Negeri 11 Bengkulu City can assist the school in searching student data to obtain information on student offenses for the last 1 school year. Based on the results of the tests that have been carried out, the functional of the student data search application at SMA Negeri 11 Bengkulu City has run well as expected and is able to provide information on the results of student data searches at school